Penambahan Peta Wisata Sebagai Pemenuhan Aksesibilitas Desa Pogalan Sebagai Desa Wisata - Arya Ade Yunanto; Drifarrosa Aisy Aufanuha Machfudz; Farah Aribah; Ilfa Sholikhah; Inggrid Bintang T H; Miftakhul Huda; Evi Gravitiani; Anugrah Adiastuti; Addina Syifa (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has dealt a heavy blow to the tourism sector in Indonesia, which is one of the pillars of the country's revenue. Whereas before the pandemic occurred, the tourism sector was growing rapidly, as in 2016 tourism contributed about 4% of total GDP and unfortunately the COVID-19 pandemic hampered its development. Pogalan village tourism, Pakis, Magelang is one of the tourism industries which is affected by the COVID-19 pandemic. Located in the Mount Merbabu National Park area, this tourist spot is quite difficult to reach in extreme weather and many tourists are not familiar with this tourist spot. Therefore, to overcome this problem, The KKN MBKM Riset Keilmuan UNS Team provides a solution in the form of making Tourist Maps to facilitate accessibility of tourists . In implementing this solution, the KKN MBKM Riset Keilmuan Team applied the Participatory Rural Appraisal (PRA) method which prioritizes the active participation of the local community and local government, namely Pogalan Village, Magelang Regency. To introduce tourist destinations in Pogalan Village, the KKN MBKM Riset Keilmuan UNS Team created a Pogalan Village Tourism Map which not only contains tourist locations but also increases accessibility for tourists to get there.